Cross-modal integration of emotions in the chemical senses - BENSAFI, Moustafa; Iannilli, Emilia; Schriever, Valentin; Seo, Han-Seok S.; Poncelet, Johan; Gerber, Johannes; Rouby, Catherine; Hummel, Thomas (Frontiers in Human Neuroscience, 2013)
Although the brain structures involved in integrating odorant and trigeminal stimuli are well documented, there is still a need to clarify 1) how emotional response is represented in the human brain during cross-modal interaction between odors and trigeminal stimuli, and 2) whether the degree of congruency between the two types of stimuli influences these emotional responses and their neural processing. These questions were explored combining psychophysics, event-related potentials (ERP) and fMRI in the same group of 17 subjects under a “congruent condition” (intranasal carbon dioxide mixed with the smell of orange, a combination found in soda drinks, for example), and an “incongruent condition” (intranasal carbon dioxide mixed with the smell of rose, a combination not encountered in everyday life). Responses to the 3 constituent stimuli (carbon dioxide, orange and rose) were also measured. Hedonic and intensity ratings were collected for all stimulations. The congruent bimodal stimulus was rated as more pleasant than the incongruent. This behavioral effect was associated with enhanced neural activity in the hippocampus and anterior cingulate gyrus, indicating that these brain areas mediate reactivation of pleasant and congruent olfactory-trigeminal associations.